Equilibrium and Kinetics Study of Adsorption of Crystal Violet onto the Peel of Cucumis sativa Fruit from Aqueous Solution - T. Smitha; S. Thirumalisamy; S. Manonmani (E-Journal of Chemistry)
The use of low-cost, locally available, high efficiency and eco-friendly adsorbents has been investigated as an ideal alternative to the current expensive methods of removing dyes from wastewater. This study investigates the potential use of the peel of Cucumis sativa fruit for the removal of crystal violet (CV) dye from simulated wastewater. The effects of different system variables, adsorbent dosage, initial dye concentration, pH and contact time were investigated and optimal experimental conditions were ascertained. The results showed that as the amount of the adsorbent increased, the percentage of dye removal increased accordingly. Optimum pH value for dye adsorption was determined as 7.0. The adsorption of crystal violet followed pseudo-second order rate equation and fit well Langmuir and Freundlich equations. The maximum removal of CV was obtained at pH 7 as 92.15% for adsorbent dose of 0.2 g/50 mL and 25 mg L-1 initial dye concentration at room temperature. The maximum adsorption capacity obtained from Langmuir equation was 34.24 mg g-1. Furthermore, adsorption kinetics of (CV) was studied and the rate of adsorption was found to conform to pseudo-second order kinetics with a good correlation (R2 > 0.9739). The peel of Cucumis sativa fruit can be attractive options for dye removal from diluted industrial effluents since test reaction made on simulated dyeing wastewater show better removal percentage of (CV).